(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
This study aims to describe the initial phase syllabus design in the context of hospitality vocational secondary school. It focuses on identifying the hospitality students’ specific needs about English and introducing ESP based instruction in the context of hospitality program. The subject of research were students and teachers taken from two vocational secondary schools. A mix method study was used as research design. In obtaining quantifiable data, interview, surveys and syllabus review were carried out in two different secondary schools. As well as semi structured interview, open ended questionnaires and syllabus review were done to provide meaningful result to this study. The theory from Gravatt, Richards and Lewis (1997) is used as a guidance to set theories and models in the tested questions and survey. Then, the data was analyzed by using SPSS for descriptive and inferential statistics. The results claimed that necessarily developing an ESP learning in hospitality program, adjusted to the students’ focus in ELT; English for hospitality. There also be concluded that ESP syllabus design was important as addressing students’ immediate needs as a language learner and their long term as professionals in the hospitality services.